Factors influencing the effectiveness of bilingual educational programs by a selected school in jaffna zone - Ganeshalingam, M. (University of Jaffna, 2020)
Bilingual education plays a significant role in society and essential for higher education, employability, or economic growth among students and societies. This research aims to investigate the factors influencing the effectiveness of higher education for human capital. Data were collected through a questionnaire and analyzed by the research is undertaken using the SPSS package. Data will convert to numerical codes and entered a predesigned data entry spreadsheet in SPSS. 75 students were randomly selected from the Jaffna zone. Theory derived from education and physiology and sociology literature for analyzing and finding. The result indicates that "behavioral, motivation" and "education level" variables have no significant influence on the bilingual education to start-up and controvert findings in prior literature. Result further expose that social networking and internal control variables could positively affect bilingual education to start up the human capital investment process. Present system of education are increasingly unhealthy for the goals. Encouraging positive mindsets, creativity, and associating with challenging new thoughts and ways of responding to adopt innovation are a critical future enhancement.
Keywords: Bilingual education; Effectiveness influence and prospects